MCSA/MCSE managing and maintaining a Windows Server 2003 environment for an MCSA certified on Windows 2000 study guide & DVD training system - Schimed, Will.; Shimonski, Robert (Rockland, MA : Syngress Pub., 2003)
MCSA/MCSE Exam 70-292 Study Guide & DVD Training System: Managing and Maintaining a Windows Server 2003 Environment for an MCSA Certified on Windows 2000 is a one-of-a-kind integration of text, DVD-quality instructor led training, and Web-based exam simulation and remediation. This system gives you 100% coverage of the official Microsoft 70-292 exam objectives plus test preparation software for the edge you need to pass the exam on your first try. In June, 2003 Microsoft will launch beta exams for the Windows Server 2003 certification line. Exams will likely go live the following August and September. This launch is a comprehensive revamping of the MCSE (Microsoft Certified System Enginner) track with all new core exams and all new electives. In addition, the MCSA (Microsoft Certified System Administrator) certification will expand its program to include an additional upgrade exam for MCSAs wanting to become MCSEs. The launch of this new certification track means that all current MCSEs, representing an installed base of approximately 200,000 (source: MCP Magazine) will need to recertify under Windows Server 2003. In addition, any MCP looking to become an MCSE--estimates are about 1.2 million (source: MCP Magazine)--will also have to continue their certifications under the new program. Many industry experts expect the Windows 2003 certification, and product line as well, to be a more popular track since many organziations are still using NT and plan to skip 2000 and go directly to 2003. * DVD Provides a "Virtual Classroom": Get the benefits of instructor led training at a fraction of the cost and hassle. * Guaranteed Coverage of All Exam Objectives: If the topic is listed in Microsoft's Exam 70-292 objectives, it is covered here. * Fully Integrated Learning: This system includes a study guide, DVD training and Web-based practice exams.
Includes index.
Keywords: Microsoft Windows server -- Examinations; Microsoft Windows server -- Certification; Computer networks -- Management -- Examinations -- Study guides; Computer networks -- Management -- Certification; Electronic books